PNPLA3 gene polymorphism accounts for fatty liver in community subjects without metabolic syndrome - Shen, J.; Wong, G. L.‐H.; Chan, H. L.‐Y.; Chan, H.‐Y.; Yeung, D. K.‐W.; Chan, R. S.‐M.; Chim, A. M.‐L.; Chan, A. W.‐H.; Choi, P. C.‐L.; Woo, J.; Chu, W. C.‐W.; Wong, V. W.‐S. (Alimentary pharmacology & therapeutics, 2014)
Summary Background The rs738409 GG variant in patatin‐like phospholipase 3 (PNPLA3) is associated with non‐alcoholic fatty liver disease (NAFLD) and disease severity. However, it remains unclear if it contributes to the development of NAFLD through affecting dietary pattern. Aim To examine the association among PNPLA3 gene polymorphism, dietary pattern, metabolic factors and NAFLD. Methods Liver fat and fibrosis were assessed by proton‐magnetic resonance spectroscopy and transient elastography in 920 subjects from a population screening project (251 had NAFLD). Dietary nutrient intake was recorded using a locally validated food‐frequency questionnaire. Results The prevalence of GG genotype in NAFLD subjects was 20.7%, compared to 10.6% in controls (P < 0.001). Macronutrient intake was similar among subjects with different PNPLA3 genotypes. The presence of G allele was a predictor of NAFLD independent of nutrient intake and other metabolic factors (adjusted odds ratio to CC: CG, 2.00; GG, 2.68). In subjects without metabolic syndrome, G allele was even more closely correlated with NAFLD diagnosis (adjusted odds ratio to CC: CG, 2.22; GG, 3.39). The prevalence of NAFLD was only 12% in subjects with CC genotype and no metabolic syndrome, and increased to 34% in those with GG genotype and no metabolic syndrome. While NAFLD subjects had significantly lower fibre intake, there was no significant interaction between PNPLA3 and dietary pattern. Conclusions The G allele in PNPLA3 rs738409 increases the risk of NAFLD in the general population, especially in subjects without metabolic syndrome, independent of dietary pattern and metabolic factors.